Regulation of neurotrophin receptor (Trk) signaling: suppressor of cytokine signaling 2 (SOCS2) is a new player - Uren, Rachel T.; Turnley, Ann M. (Frontiers in Molecular Neuroscience, 2014)
The classic neurotrophins Nerve Growth Factor (NGF), Brain Derived Neurotrophic Factor (BDNF) and Neurotrophins NT-3 and NT-4 are well known to regulate various aspects of neuronal differentiation, survival and growth. They do this by binding to their cognate receptors, members of the Tropomyosin-related kinase (Trk) receptor tyrosine kinase family, namely TrkA, TrkB and TrkC. These receptors are then internalized and localized to different cellular compartments, where signal transduction occurs. Conversely, members of the suppressor of cytokine signaling (SOCS) family are best known as negative regulators of signaling via the JAK/STAT pathway. Some members of the family, and in particular SOCS2, have roles in the nervous system that at least partially overlap with that of neurotrophins, namely neuronal differentiation and neurite outgrowth. Recent evidence suggests that SOCS2 is a novel regulator of NGF signaling, altering TrkA cellular localization and downstream signaling to affect neurite growth but not neuronal survival. This review first discusses regulation of Trk receptor signaling, followed by the role of SOCS2 in the nervous system and finishes with a discussion of possible mechanisms by which SOCS2 may regulate TrkA function.